Analisis Implementasi Kebijakan Pemungutan Pajak Hiburan Dalam Meningkatkan Penerimaan Pajak Daerah Pada Suku Badan Pajak dan Retribusi Daerah Jakarta Utara Tahun 2015-2017 - Sofiatul Laily; Edy Edy (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This research was conducted to analyze the Implementation of Entertainment Tax policy in the Taxation and Retribution Agency Jakarta Utara, obstacles faced, and the efforts made by the Taxation and Retribution Agency Jakarta Utara to increase revenue from Entertainment Tax in Jakarta Utara. This study used a descriptive qualitative method with the object of research based on primary data (interviews) and secondary data (field research). The study used the theory of Edward III which was synthesized by the theory of Van Meters and Van Horn so that there were seven variables related to the implementation of Tax Entertainment policy which were, Communication, Resources, Disposition, Bureaucratic Structure, Policy Standards and Objectives, Characteristics of Implementing Agents, and Social Conditions and Economy. The results of this study indicated that the implementation of the entertainment tax policy has not run optimally, because it is still constrained in the communication aspect, which is the lack of direct socialization to taxpayers which causes the lack of understanding of taxpayers regarding local taxes, from the aspect of information, the obstacles come from the entertainment providers who have not registered and who have not registered their entertainment business as an object of tax, as well as the lack of human resources in supervising the implementation of the policy, this affects the revenues from entertainment tax. The writer suggests to improve the quality of tax officers, hold socialization directly to the public, and the officers must work directly in the field to monitor the implementation of entertainment tax.